The most important components of out-of-hours community care for patients at the end of life: A Delphi study of healthcare professionals' and patient and family carers' perspectives. (September 2022) - Goodrich, Joanna; Tutt, Lydia; Firth, Alice M; Evans, Catherine J; Murtagh, Fliss EM; Harding, Richard
Background: Community services for palliative patients outside normal working hours are variable and the best evidence-based models of care have not been determined. Aim: To establish expert consensus on the most important components of out-of-hours community palliative care services. Design: Delphi study. The first round listed 68 components generated from systematic literature reviewing, focus groups with healthcare professionals and input from the project's patient and public involvement advisory group. The components deemed 'essential' by over 70% of participants in the first round were refined and carried forward to a second round, asking participants to rank each on a five-point Likert scale (5 highest to 1 lowest). The consensus threshold was median of 4 to 5 and interquartile range of ⩽1. Participants: Community specialist palliative care health professionals, generalist community health professionals and patients and family carers with experience of receiving care out-of-hours at home. Results: Fifty-four participants completed round 1, and 44 round 2. Forty-five components met the threshold as most important for providing out-of-hours care, with highest consensus for: prescription, delivery and administration of medicines; district and community nurse visits; and shared electronic patient records and advance care plans. Conclusions: The Delphi method identified the most important components to provide community palliative care for patients out-of-hours, which are often provided by non-specialist palliative care professionals. The importance placed on the integration and co-ordination with specialist palliative care through shared electronic records and advance care plans demonstrates the reassurance for patients and families of being known to out-of-hours services.